'n Genre-omlyning van die chanson - Elisabeth Snyman (Communicare)
The aim of this article, held at a popular culture symposium in honour of the Afrikaans writer Hennie Aucamp, is to define the  genre of the chanson with specific reference to the poetic chanson of Jacques Brel. Taking the moment of interpretation as point of depar ture, it is argued that the chanson is an inter disciplinary genre combining specific elements of theatre, poetry and music to com municate not only orally, but also audio-visually with an audience. Findings of the semiotics of theatre are used to demonstrate how the chanson uses more than words to put its message across.